Electron transport system of an aerobic carbon monoxide-oxidizing bacterium. - Kim, Y M (1981)
Experiments with crude extracts of Pseudomonas carboxydohydrogena revealed that a quinone is necessary for CO oxidation, and that cytochromes of the a, b, and c types and functional terminal oxidase(s) are found in cells grown on CO as the sole source of carbon and energy. CO dehydrogenase delivers electrons to the electron transport system at the level of quinone, and nicotinamide adenine dinucleotide (phosphate) is not involved in CO oxidation.